2006
DOI: 10.1007/s11249-006-9057-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-environmental lubrication performance and lubrication mechanism of MoS2/Sb2O3/C composite films

Abstract: MoS 2 -Sb 2 O 3 -C composite films exhibit adaptive behavior, where surface chemistry changes with environment to maintain the good friction and wear characteristics. In previous work on nanocomposite coatings grown by PVD, this type of material was called a ''chameleon'' coating. Coatings used in this report were applied by burnishing mixed powders of MoS 2 , Sb 2 O 3 and graphite. The solid lubricant MoS 2 and graphite were selected to lubricate over a wide and complementary range including vacuum, dry air a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…It implies that the surface material modification occurred by atomic rearrangements in the sliding interface and resulted in the recrystallization and reorientation of the film. This data from the sliding contact sample without counterpart separation is consistent with prior cross-sectional TEM [24,25,[31][32][33] and X-ray diffraction [48] measurements on separated contact samples, and undoubtedly validates the prior results. The tribological film formation could be confined in a few atomic layers in terms of the recrystallization and reorientation of (002) basal planes.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It implies that the surface material modification occurred by atomic rearrangements in the sliding interface and resulted in the recrystallization and reorientation of the film. This data from the sliding contact sample without counterpart separation is consistent with prior cross-sectional TEM [24,25,[31][32][33] and X-ray diffraction [48] measurements on separated contact samples, and undoubtedly validates the prior results. The tribological film formation could be confined in a few atomic layers in terms of the recrystallization and reorientation of (002) basal planes.…”
Section: Resultssupporting
confidence: 86%
“…Cross-sectional TEM showed that the hexagonal MoS 2 -basal planes aligned parallel to the wear scar surface. This was observed in magnetron sputtered MoS 2-x films [24], ion beam sputtered MoS x films [25], dual ion beam deposited Pb-Mo-S films [31], burnished MoS 2 /Sb 2 O 3 /C composite films [32], and PLD MoS 2 /Sb 2 O 3 multilayer films [33]. The post-test analyses inevitably involved the separation of sliding contact surfaces as part of the sample preparation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…All of the normal and frictional forces are measured using a multiaxial load-cell that is rigidly mounted to the pin sample. The stage and stepper motor assembly is used to position the sample under the microscope objective develop a thin layer of MoS 2 basal planes oriented parallel to the surfaces during running-in, after which the wear process is a minimum [29]. The established interfacial surfaces relative motion is then likely governed by surface potential interactions of MoS 2 sliding against itself.…”
Section: Measurements Of Steady-state Wear Rates In Mos 2 Coatingsmentioning
confidence: 99%
“…A number of metal or oxide dopants in MoS 2 have also been successfully tried. Notable examples of dopants include: Ti [17][18][19][20][21], Al [22,23], Ni [24][25][26], Au [8,24,26], Pb [24,27,28], PbO [24,29,30], Sb 2 O 3 [25,[30][31][32][33][34][35]. The presence of these dopants can lead to increased coating density, hardness, and oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%